The Uses and the Limits of the Short Story: The Function of Character Migration in Alice Munro’s Lives of Girls and Women - Jacob HOVIND (E-REA)
This article explores the phenomenon of character migration in one of Alice Munro’s early works, Lives of Girls and Women from 1971. Munro vitally maintains the typical structure of the modern Anglo-American short story, with its tendency toward condensation and building toward its ending, as well as the form’s thematic principle of the epiphany concept. But she also allows her characters to live beyond each individual story, showing how they survive their climactic epiphanies and incorporate them into the larger narrative of their lives. In so doing, Munro challenges the usual distinction between the novel and the short story, illuminating what each genre is uniquely equipped to perform in terms of the presentation of character, while also suggesting the limits inherent in each.